2021
DOI: 10.1021/acs.langmuir.0c03676
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Gas–Solid Sorption Properties of Geologic Materials Using Inverse Gas Chromatography

Abstract: The goal of this study was to determine the physicochemical properties of a variety of geologic materials using inverse gas chromatography (IGC) by varying probe gas selection, temperature, carrier gas flow rate, and humidity. This is accomplished by measuring the level of interaction between the materials of interest and known probe gases. Identifying a material’s physicochemical characteristics can help provide a better understanding of the transport of gaseous compounds in different geologic materials or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Characterizing the properties of individual organic and inorganic components can help elucidate the primary factors influencing volatile interactions in more complex mixtures. Recent work has demonstrated that IGC is effective in analyzing key physicochemical parameters (e.g., partition coefficient, diffusion coefficient, and heat of adsorption) used for modeling subsurface gas transport [1]. Ongoing efforts involve integrating IGC-determined physicochemical parameters with Subsurface Transport Over Multiple Phases-GeoThermal (STOMP-GT, [2]) models to better predict vapor transport through the subsurface (Figure 2).…”
Section: Elucidating Physicochemical Properties Of Geologic Materials...mentioning
confidence: 99%
“…Characterizing the properties of individual organic and inorganic components can help elucidate the primary factors influencing volatile interactions in more complex mixtures. Recent work has demonstrated that IGC is effective in analyzing key physicochemical parameters (e.g., partition coefficient, diffusion coefficient, and heat of adsorption) used for modeling subsurface gas transport [1]. Ongoing efforts involve integrating IGC-determined physicochemical parameters with Subsurface Transport Over Multiple Phases-GeoThermal (STOMP-GT, [2]) models to better predict vapor transport through the subsurface (Figure 2).…”
Section: Elucidating Physicochemical Properties Of Geologic Materials...mentioning
confidence: 99%